SOCIAL MEDIA AND THE AVAILABILITY OF HEALTH SERVICES AS THE DOMINANT FACTOR ON THE USAGE OF VAGINAL DOUCHING BASED ON MARITAL STATUS - Zidni Hasbuna Shabran; Bambang Purwanto; Atika Atika (Universitas Airlangga, 2022)
The practice of vaginal douching remains as one of the most attentive topics in the public health domain. The prevalence of vaginal douching in Indonesia about 75% both married and unmarried, despite its risks towards health and well being. This practice can be prevented and avoided by managing the factors behind its practice, which were studied through consideration of the role of social media, health services, knowledge, attitude, culture, and experience. The purpose of this study is to identify the major factors behind the practice of vaginal douching among women according to their marital status. This research was designed as an observational analysis study with cross sectional survey and 152 samples were collected with simple random sampling. Bivariate analysis were done using Chi-square while multivariate analysis were done with logistic regression to determine the dominant factor behind the practice. Factors being considered in the analysis were social media, health services, knowledge, attitude, culture, and experience. The most significant factors according to marital status were social media (OR = 6,2; CI: 1,83 – 21,11; p value = 0,003) and health services (OR = 3,0; CI: 1,23 – 7,42; p value = 0,016).